2016
DOI: 10.1080/01443615.2016.1228622
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between functional ovarian cysts and vitamin A, vitamin E, and folate intake

Abstract: This study aimed to clarify the relationship between functional ovarian cysts and vitamin A, vitamin E, and folate intake. This case-control study evaluated 265 women of reproductive age who presented at gynaecology clinics of three hospitals in Mashhad, Iran. While women in the ovarian cyst group [n = 132] had functional ovarian cysts, control group [n = 133] consisted of women without functional ovarian cysts. The participants' vitamin A, vitamin E, and folate intake was assessed using the Food Frequency Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Certain studies have suggested an increased risk of ovarian cancer associated with higher fat intake, although the results are dependent on the type of fat consumed [2]. For instance, a study by Britton et al on women aged 17 to 74 in the United States found that higher consumption of vegetable oils and polyunsaturated fats was associated with an increased likelihood of multiple endometriosis, serous, and teratoma occurrence [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have suggested an increased risk of ovarian cancer associated with higher fat intake, although the results are dependent on the type of fat consumed [2]. For instance, a study by Britton et al on women aged 17 to 74 in the United States found that higher consumption of vegetable oils and polyunsaturated fats was associated with an increased likelihood of multiple endometriosis, serous, and teratoma occurrence [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cysts are sacs, with or without fluid, located inside the ovary or on its surface [1]. A prevalent gynecological disorder among females of reproductive age is functional ovarian cysts (FOCs) [2]. The American Gynecological & Obstetrical Society reports that FOCs have a prevalence of 7%, and approximately 1 in 25 women become symptomatic [3].…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] The functional ovarian cysts are the most common ovarian masses of reproductive age and are influenced by the ovarian cycle and hormonal changes. [ 23 , 24 ] Most corpus luteum cysts are asymptomatic and will resolve spontaneously in the absence of pregnancy or after the first trimester of pregnancy, or after placental maturation. [ 22 ] However, it is still possible for the corpus luteum cysts to rupture or twist, causing acute abdominal pain and pelvic bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian follicles are primarily responsible for the synthesis and secretion of reproductive hormones, estradiol, and progesterone. 55 These sex steroids exhibit essential roles in the management of uterine cell proliferation, the stromal-epithelial cells cross-talk, and the required differentiation for appropriate pregnancy preparation. 56,57 Therefore, based on the role of the ovary in maintaining uterine homeostasis, the prevention of toxicity in the ovary by these antioxidants may lead to healthy uterine tissue.…”
Section: Discussionmentioning
confidence: 99%